Satellite telemetry and digital aerial surveys show strong displacement of red-throated divers (Gavia stellata) from offshore wind farms. (September 2020) - Heinänen, Stefan; Žydelis, Ramūnas; Kleinschmidt, Birgit; Dorsch, Monika; Burger, Claudia; Morkūnas, Julius; Quillfeldt, Petra; Nehls, Georg
Abstract: Expansion of offshore wind energy is vital for the reduction of CO2 emissions. However, offshore wind farms may negatively impact the environment without proper planning. Here we assess the robustness of the conclusions of earlier studies that the strictly protected red-throated diver, Gavia stellata, is strongly displaced from wind farms in the German Bight (North Sea). We modelled the distribution of divers based on two independent data sets, digital aerial surveys and satellite telemetry, in relation to the dynamic offshore environment and anthropogenic pressures. Both data types found that divers were strongly displaced from wind farms in suitable habitat. The displacement effect gradually decreased with distance from the wind farms (being very strong up to 5 km away), but a significant effect could be detected up to 10–15 km away. The telemetry data further indicated that the displacement distance decreased with decreasing visibility. The displacement distance was also shorter during the day than during the night, potentially as a response to aviation and navigation lights of the wind farms. These findings should be taken into consideration in marine spatial planning to avoid cumulative impacts on red-throated diver populations. Highlights: Red-throated divers are strongly displaced from offshore wind farms. Models based on telemetry and digital aerial survey data showed highly similar results. Dynamic species distribution modelling was applied. Displacement distance decreased with decreasing visibility.